Tradisi Ngosek Ponjen: Refleksi Ajaran Islam dan Budaya Lokal pada Masyarakat Osing Banyuwangi: Ngosek Ponjen Tradition: Reflection of Islamic Teachings and Local Culture in the Osing Community of Banyuwangi - M. Syamsudini (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2011)
The Ngosek Ponjen or Perang Bangkat tradition is a marriage ritual of the Osing Banyuwangi community for the youngest child (kemunjilan) who marries another youngest child or one of them is the youngest, with the hope that their married life will be happy. This tradition is filled with advice from the customary elders, reflected in every process of the tradition and the selected offerings. These offerings include peras pikul, peras suwun, pillows, bamboo mats, romesan, kinangan, cigarettes, earthen jugs, scented water, eggs, chickens, petarangan, stones, and a broom (sapu kerek). In terms of timing, this tradition is performed during the meeting (temon) of the bridal procession at dawn after the marriage oath is conducted first. The Ngosek Ponjen or Perang Bangkat cultural tradition is interesting to research because the Osing community uses this tradition as a form of religious understanding combined with local traditions through rituals and offerings (peras/sesojen). Tradisi Ngosek Ponjen atau Perang Bangkat adalah ritual pernikahan masyarakat Osing Banyuwangi untuk anak bungsu (kemunjilan) yang menikah dengan sesama anak bungsu atau salah satunya adalah anak bungsu, dengan harapan kehidupan rumah tangga mereka akan bahagia. Tradisi ini sarat dengan nasihat-nasihat dari para tetua adat yang tercermin dalam setiap prosesi tradisi dan sesajen yang dipilih. Sesajen tersebut meliputi peras pikul, peras suwun, bantal, tikar bambu, romesan, kinangan, rokok, kendi tanah, air wewangian, telur, ayam, petarangan, batu, dan sapu kerek. Dari segi waktu, tradisi ini dilaksanakan saat pertemuan (temon) prosesi pengantin pada subuh hari setelah akad nikah dilakukan terlebih dahulu. Tradisi budaya Ngosek Ponjen atau Perang Bangkat ini menarik untuk diteliti karena masyarakat Osing menggunakan tradisi ini sebagai bentuk pemahaman agama yang mereka gabungkan dengan tradisi lokal melalui ritual dan sesajennya (peras/sesojen).